Types of X-Ray Studies - Dalimbekovna, Latipova Kamila (American Journal of Bioscience and Clinical Integrity, 2025)
This paper examines radiography, which uses ionizing radiation to obtain images of the internal structure of various parts of the body. It is shown that modern X-ray machines deliver minimal radiation doses, making the examination relatively safe. This method provides high information yield, allowing the physician to quickly assess the condition of the anatomical area of interest. Images can also be obtained in just a few minutes, allowing for rapid treatment initiation or adjustments to existing treatment plans.